Sharia Supervisory Boards as Mechanisms of Religious Governance: A Qualitative Analysis of DPS Reports and Disclosures in Southeast Asian Islamic Banks - Santiadji Mustafa; Ahmad Sani; Darwis Said; Syarifuddin (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines how Sharia Supervisory Boards (DPS) communicate their religious governance roles in Islamic banks across Southeast Asia. Method: Using a comparative qualitative approach, the analysis is based on DPS reports, regulatory frameworks, and AAOIFI governance standards from 2020 to 2024. Results: The results show regional convergence in core disclosure elements such as annual Shariah opinions, religious framing, and formal oversight statements. Malaysia and Brunei demonstrate the highest narrative detail and transparency, while Indonesia employs concise doctrinal reporting and Thailand presents minimal disclosure. The study reveals that DPS communication serves as a hybrid mechanism combining spiritual accountability, procedural assurance, and legitimacy construction. Variations across countries are shaped by institutional maturity, regulatory environments, and the strength of governance expectations. These findings contribute to a nuanced understanding of how Shariah governance is performed through narrative reporting in Southeast Asian Islamic banks. Conclusion: This study examined how Dewan Pengawas Syariah (DPS) express and communicate their religious governance roles across Islamic banks in Southeast Asia by analyzing formal DPS reports and related governance documents from Indonesia, Malaysia, Brunei Darussalam, and Thailand. The findings show that DPS consistently construct their role through a combination of devotional language, compliance declarations, and the articulation of oversight responsibilities, reflecting a shared foundation of Islamic accountability. While religious expressions vary in richness and placement, all jurisdictions employ them to signal ethical integrity and alignment with divine and public expectations. Oversight narratives likewise form a core part of DPS communication, although the depth of disclosure differs substantially across countries. Collectively, these patterns reveal that DPS reports function as both spiritual statements and institutional instruments of governance